Correlation between vitamin D and poor sleep status in restless legs syndrome - Geng, Chaofan; Yang, Zhenzhen; Kong, Xiumei; Xu, Pengfei; Zhang, Hongju (Frontiers in Endocrinology, 2022)
Background Restless Legs Syndrome (RLS) is closely related to poorer sleep quality. Vitamin D can regulate sleep regulation, cell proliferation, and differentiation. To measure whether vitamin D has predictive value for poor sleep quality in RLS was our aim in this study. Methods To analyze the serum levels of 25-hydroxyvitamin D [25(OH)D] in 95 RLS patients. We used the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality. Subjects had been divided into a normal and poor-sleeper groups according to the PSQI score. Using correlation and regression analysis to explore underlying etiologies that affect sleep disorder in RLS patients. Results Patients in the poor-sleeper group had significantly lower vitamin D levels in comparison to the normal group. The serum vitamin D levels were negative correlate with PSQI scores after adjusting for confounding factors. In addition, regression analysis showed that vitamin D could act as a predictor for sleep disorders in RLS patients (odds ratio [OR] = 0.008, p = 0.004). The area under the curve (AUC), cut-off value, sensitivity, and specificity of serum vitamin D was 0.967 (95% CI 0.935–0.998), 16.84 ng/ml, 87.5%, and 93.7% by receiver operating characteristic (ROC) analysis. Conclusion Our study confirmed the relationship between poorer sleep quality and vitamin D in RLS. However, the causal relationship between vitamin D deficiency and RLS is currently inconclusive. The effect of vitamin D supplementation is needed to confirm as the therapeutic strategies for sleep disorders in RLS patients in future work.